Zika virus vaccines. Issue 10 (October 2018) - Abbink, Peter; Stephenson, Kathryn; Barouch, Dan
Abstract The recent epidemic of Zika virus (ZIKV) in the Americas has revealed the devastating consequences of ZIKV infection, particularly in pregnant women. Congenital Zika syndrome, characterized by malformations and microcephaly in neonates as well as developmental challenges in children, highlights the need for the development of a safe and effective vaccine. Multiple vaccine candidates have been developed and have shown promising results in both animal models and phase I clinical trials. However, important challenges remain for the clinical development of these vaccines. In this Progress article, we discuss recent preclinical studies and lessons learned from first-in-human clinical trials with ZIKV vaccines. The recent epidemic of Zika virus (ZIKV) in the Americas has revealed the devastating consequences of ZIKV infection, particularly in pregnant women. In this Progress article, Barouch and colleagues discuss recent preclinical studies and lessons learned from first-in-human clinical trials with ZIKV vaccines.